2023
DOI: 10.3390/vaccines11081292
|View full text |Cite
|
Sign up to set email alerts
|

Development and Immunoprotection of Bacterium-like Particle Vaccine against Infectious Bronchitis in Chickens

Abstract: Infectious bronchitis (IB) is a major threat to the global poultry industry. Despite the availability of commercial vaccines, the IB epidemic has not been effectively controlled. The exploration of novel IBV vaccines may provide a new way to prevent and control IB. In this study, BLP-S1, a bacterium-like particle displaying the S1 subunit of infectious bronchitis virus (IBV), was constructed using the GEM-PA surface display system. The immunoprotective efficacy results showed that BLP-S1 can effectively induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 44 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Scientists usually use it together with immunopotentiators when preparing vaccines to improve immunogenicity (Khalaj-Hedayati et al, 2020;Wang et al, 2021;Mekonnen et al, 2022). Studies have confirmed that BLP is an effective immunopotentiator, and the BLP surface display platform has also been applied to the development of vaccines for various diseases Su et al, 2023;Wang et al, 2023;Zhang et al, 2023). There are very few anchoring proteins available for the BLP surface display platform, though.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scientists usually use it together with immunopotentiators when preparing vaccines to improve immunogenicity (Khalaj-Hedayati et al, 2020;Wang et al, 2021;Mekonnen et al, 2022). Studies have confirmed that BLP is an effective immunopotentiator, and the BLP surface display platform has also been applied to the development of vaccines for various diseases Su et al, 2023;Wang et al, 2023;Zhang et al, 2023). There are very few anchoring proteins available for the BLP surface display platform, though.…”
Section: Discussionmentioning
confidence: 99%
“…BLP is a type of immunopotentiator with enormous potential in vaccine development ( Heine et al, 2015 ). Because of their high safety, mucosal delivery efficiency, and adjuvant effect, BLP is widely used in the production of mucosal adjuvants and mucosal vaccines ( Zhang et al, 2022 ; Su et al, 2023 ; Wang et al, 2023 ; Zhang et al, 2023 ). There is a need to expand the range of mucosal vaccines based on BLP because there are currently few available due to the high technical requirements.…”
Section: Introductionmentioning
confidence: 99%